2022
DOI: 10.3390/biom12111674
|View full text |Cite
|
Sign up to set email alerts
|

Osteoglycin: An ECM Factor Regulating Fibrosis and Tumorigenesis

Abstract: The extracellular matrix (ECM) is made up of noncellular components that have special properties for influencing cell behavior and tissue structure. Small leucine-rich proteoglycans (SLRPs) are nonfibrillar ECM components that serve as structural scaffolds and signaling molecules. osteoglycin (OGN), a class III SLRP, is a ubiquitous ECM component that not only helps to organize the extracellular matrix but also regulates a number of important biological processes. As a glycosylated protein in the ECM, OGN was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…Mimecan, also known as osteoglycin (OGN), belongs to the class III of small leucine-rich proteoglycans, a group of extracellular matrix (ECM) components. OGN is an important regulatory protein, it is expressed in many organs and it participates in the regulation of bone and collagen formation, and vascular remodelation [28][29][30][31]. The relationship of OGN to tumorigenesis has already been reported by many studies, but the dynamics of expression vary in different tumors.…”
Section: Biological and Clinical Importance Of The Selected Identifie...mentioning
confidence: 99%
“…Mimecan, also known as osteoglycin (OGN), belongs to the class III of small leucine-rich proteoglycans, a group of extracellular matrix (ECM) components. OGN is an important regulatory protein, it is expressed in many organs and it participates in the regulation of bone and collagen formation, and vascular remodelation [28][29][30][31]. The relationship of OGN to tumorigenesis has already been reported by many studies, but the dynamics of expression vary in different tumors.…”
Section: Biological and Clinical Importance Of The Selected Identifie...mentioning
confidence: 99%
“…Whether increasing the concentration of biglycan by upregulating its endogenous expression or systemic administration exerts antitumor effects by enhancing antitumoral immune responses still needs to be determined. 159 In addition to the role of mimecan in atherosclerosis and TLR-mediated proinflammatory signaling (described in the preceding section of this review), mimecan regulates tissue fibrosis and tumorigenesis (extensively reviewed recently 169,170 ). Deficiency of mimecan exacerbated myocardial fibrosis and dysfunction by enhancing the proliferation and migration of cardiac myofibroblasts in angiotensin II-induced hypertension in mice.…”
Section: Role Of Matricellular Proteoglycans In Wound Healing Maligna...mentioning
confidence: 99%
“…172 Expression of mimecan is downregulated in colon, breast, liver and cervical cancers, whereas its expression is increased in ovarian cancer and melanoma. 169 High expression of mimecan in the tumor tissue is associated with prolonged survival of patients with colorectal cancer. Further, it was observed that mimecan suppresses tumor growth by inhibiting vascular endothelial growth factor-driven angiogenesis and epithelial-tomesenchymal transition and increasing T-cell recruitment, 173,174 suggesting that enhancing the bioavailability of mimecan, either by upregulating its endogenous expression or by systemic administration, works as a potential antitumor therapeutic strategy.…”
Section: Role Of Matricellular Proteoglycans In Wound Healing Maligna...mentioning
confidence: 99%
See 2 more Smart Citations